2017
DOI: 10.1038/s41598-017-15702-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and characterization of the complete mitochondrial genome of Japanese Swellshark (Cephalloscyllium umbratile)

Abstract: To further comprehend the genome features of Cephalloscyllium umbratile (Carcharhiniformes), an endangered species, the complete mitochondrial DNA (mtDNA) was firstly sequenced and annotated. The full-length mtDNA of C. umbratile was 16,697 bp and contained ribosomal RNA (rRNA) genes, 13 protein-coding genes (PCGs), 23 transfer RNA (tRNA) genes, and a major non-coding control region. Each PCG was initiated by an authoritative ATN codon, except for COX1 initiated by a GTG codon. Seven of 13 PCGs had a typical T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 69 publications
(55 reference statements)
2
15
0
Order By: Relevance
“…The comparison of synonymous (Ks) and nonsynonymous (Ka) substitution rates in PCGs, evidenced for darwinian selection and adaptive molecular evolution in vertebrates 62 64 . The ratio of Ka/Ks was generally known as an indicator of selective pressure and evolutionary relations at molecular level among the homogenous or heterogeneous species 65 . It is reported that, for positive selection Ka/Ks > 1, for neutrality Ka/Ks = 1, and for negative selection Ka/Ks < 1 66 .…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of synonymous (Ks) and nonsynonymous (Ka) substitution rates in PCGs, evidenced for darwinian selection and adaptive molecular evolution in vertebrates 62 64 . The ratio of Ka/Ks was generally known as an indicator of selective pressure and evolutionary relations at molecular level among the homogenous or heterogeneous species 65 . It is reported that, for positive selection Ka/Ks > 1, for neutrality Ka/Ks = 1, and for negative selection Ka/Ks < 1 66 .…”
Section: Resultsmentioning
confidence: 99%
“…ND1, ND2, and ND6 genes might have high evolutionary rates among the three species, while COXI-III and Cytb were low. The value of nonsynonymous substitution (Ka)/synonymous substitution (Ks) is a common indicator to assess selective pressure and evolutionary relationships of species in molecular studies [52]. Ka/Ks < 1, Ka/Ks = 1, and Ka/Ks > 1 were represented purifying selection, neutral mutation and positive selection, respectively [53].…”
Section: Variations Genetic Distance and Evolution Rates Of Pcgsmentioning
confidence: 99%
“…The genomic DNA extracts from standard phenol/chloroform method (Sambrook and Russel 2000). The method for preparing and sequencing the DNA library is referred to Zhu, Liang, et al (2017). For mtDNA sequence assemble, annotation and analysis are referred to .…”
mentioning
confidence: 99%